2021
DOI: 10.1002/chem.202100450
|View full text |Cite
|
Sign up to set email alerts
|

Interconnectivity between Surface Reactivity and Self‐Assembly of Kemp Elimination Catalyzing Nanorods

Abstract: Understanding the fundamental facts behind dynamicity of catalytic processes has been a longstanding quest across disciplines. Herein, we report self-assembly of catalytically active gold nanorods that can be regulated by tuning its reactivity towards a proton transfer reaction at different pH. Unlike substrate-induced templating and cooperativity, the enhanced aggregation rate is due to alteration of catalytic surface charge only during reactivity as negatively charged transition state of reactant (5-nitroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…It has been shown in earlier literature reports that the Kemp elimination (KE) reaction can be catalyzed in cationic miceller or vesicular media in the presence of a nucleophilic anionic base . Recently, we have also demonstrated that CTAB-functionalized GNP can accelerate the KE reaction by more than 2 orders of magnitude in the presence of phosphate buffer, where phosphate ion acts as the base on the surface of the GNP . Interestingly, the immediate surface environment of the cationic nanoparticle can be modulated by relying on self-assembly of anionic peptides or phosphates, which has been discussed in previous literature. , In fact, this strategy has been utilized for the development of innovative biosensors and catalysts for one particular kind of reaction (like ester hydrolysis) using the self-assembled nanoarchitecture. , Herein, we argued that the surface environment of the CTAB-functionalized cationic GNP can be altered by using a similar type of self-assembly approach but by changing the number of the phosphate units, so that the GNP can make itself host for multiple reactions .…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…It has been shown in earlier literature reports that the Kemp elimination (KE) reaction can be catalyzed in cationic miceller or vesicular media in the presence of a nucleophilic anionic base . Recently, we have also demonstrated that CTAB-functionalized GNP can accelerate the KE reaction by more than 2 orders of magnitude in the presence of phosphate buffer, where phosphate ion acts as the base on the surface of the GNP . Interestingly, the immediate surface environment of the cationic nanoparticle can be modulated by relying on self-assembly of anionic peptides or phosphates, which has been discussed in previous literature. , In fact, this strategy has been utilized for the development of innovative biosensors and catalysts for one particular kind of reaction (like ester hydrolysis) using the self-assembled nanoarchitecture. , Herein, we argued that the surface environment of the CTAB-functionalized cationic GNP can be altered by using a similar type of self-assembly approach but by changing the number of the phosphate units, so that the GNP can make itself host for multiple reactions .…”
mentioning
confidence: 77%
“…However, a slight loss of colloidal stability of cationic GNP at 0.3 mM of ATP can be attributed to a reduction of the ξ-value below 30 mV (Figure 2b, Figure S7, SI). 15,19 It also suggests the effectiveness of binding increased with increasing valency, that is, simultaneous interaction with multiple charged phosphates like ATP. 6 We have also measured the amount of nucleotides (when added at 0.2 mM concentration) that is bound on the surface of GNP.…”
mentioning
confidence: 99%
See 3 more Smart Citations